LEVEL KONTAMINASI SENYAWA ORGANOTIN DI PRODUK SEAFOOD DARI INDONESIA - Sudaryanto, Agus (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2002)
Contamination level of TBT and DBT in seafood products such as fish and mussels collected from several locations in Indonesia were compared with Indonesian Tolerable Average Residue Levels (TARL). TARL were calculated based on the Tolerable Daily Intake (TDI) of TBT and the seafood consumption of the average consumer in Indonesia. TARL for TBT in seafood from Indonesia is 360 ng/g per day for a person with an average body weight of 60 kg. Level concentration of TBT and TBT+DBT in fish and mussels from Indonesia still below the TARL for Indonesia. However these concentration levels have been increased to those from 1995 and indicating field ecotoxicological impact of TBT has been observed as occurring gastropod imposex in Eastern Indonesia. Therefore continuing research and significant study planning with cover more areas and variety of species of seafood products are needed.